Clinico demographic profile of newly diagnosed HIV sero positive patients attending an ART centre: a cross sectional study - Gorantla, Misha; Kondagunta, Nagaraj (International Journal Of Community Medicine And Public Health, 2017)
Background: India faces a high burden of HIV. An understanding of the determinants of this disease is of vital importance in curtailing this epidemic. The objective was to study the clinico-demographic profile of the study subject. Methods: This is a cross sectional study done on 142 patients which includes all newly diagnosed (diagnosed on or after 1st January 2012), sero positive, adult patients, enrolled at ART centre, Nalgonda and started on treatment during the months of December 2012, January 2013, February 2013. A pre designed, pre tested questionnaire was used. Data regarding their demographic characteristics and various clinical aspects was obtained. Results: Out of a total of 142 study subjects, majority (78.88%) belonged to economically productive age group (16-45 years). Married individuals constituted a majority (79.57%). A majority of the subjects were skilled laborers, belonged to lower middle class of BG Prasad classification, hailed from rural areas and belonged to nuclear families. Very few had high educational attainment. A majority (95.78%) reported not using condoms during their last sexual act and 9.16% subjects reported being previously diagnosed with an STD. Most common presenting complaint was fever and most common opportunistic infections were candidiasis and tuberculosis. Majority were found to belong to stage 1 HIV. Participants were mostly underweight and had severe anaemia. Majority had CD4 count between 201- 350 cells/mm3. Conclusions: Interventions targeting improvement in socio economic status, education levels, nutritional status as well as awareness about condom use must be built into the national HIV programme.